Dampak Globalisasi Dalam Mempengaruhi Ekonomi Nasional Melalui Pandangan Ekonomi Politik - Bonaraja Purba; Anjel Ezania Sihombing; Nazwa Fazirah Nasution; Arnol Prabowo Siagian (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
In the era of globalization, interactions between countries have become increasingly complex and interrelated, playing a crucial role in shaping national economic dynamics. In the context of political economy, globalization has had a significant impact on economic structures, trade policies, and the distribution of wealth at the national level. This article illustrates how globalization, through a political economy lens, influences a country's economic resilience and raises critical questions regarding distributive justice and economic inequality. This analysis also investigates the role of the government in shaping national economic policy, as well as the challenges faced by the Indonesian state in responding to the dynamics of globalization. By understanding the complex interactions between economic and political factors, this article aims to provide deeper insight into the impact of globalization on national economies.